2018
DOI: 10.1136/bcr-2017-222917
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic abscess: a rare complication of staghorn calculi

Abstract: A staghorn calculus is a calculus accommodating the majority of a renal calyx extending into the renal pelvis. A conservative approach to its treatment may lead to high morbidity and mortality rates. Such morbidity usually manifests with renal failure, obstructed upper urinary tractand/or life-threatening sepsis. Prostatic abscesses have never been associated with staghorn calculi in the literature. We report a case of a 70-year-old man who presented with sepsis, which was found to originate from a complex pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Other less commonly reported spreading sites of peri- or perinephric abscesses include the retroperitoneum [ 18 ], psoas muscle [ 19 ], vena cava, and renal vein causing infectious thrombosis [ 20 ]. The involvement of more distant structures, such as the spleen [ 21 ], prostate [ 22 ], and lungs and bronchi, with the formation of nephron-bronchial fistulae [ 23 ] has also been occasionally observed.…”
Section: Discussionmentioning
confidence: 99%
“…Other less commonly reported spreading sites of peri- or perinephric abscesses include the retroperitoneum [ 18 ], psoas muscle [ 19 ], vena cava, and renal vein causing infectious thrombosis [ 20 ]. The involvement of more distant structures, such as the spleen [ 21 ], prostate [ 22 ], and lungs and bronchi, with the formation of nephron-bronchial fistulae [ 23 ] has also been occasionally observed.…”
Section: Discussionmentioning
confidence: 99%
“…Dakdouki et al [64] stated that Brucellosis is a multi-system disease which tends to be endemic in many Mediterranean countries including Lebanon. Nevertheless, human Brucella prostate abscess had not been previously reported in the English medical literature.…”
mentioning
confidence: 99%
“…Nevertheless, human Brucella prostate abscess had not been previously reported in the English medical literature. Dakdouki et al [64] reported the case of a young man who had manifested with fever and urinary symptoms, and who subsequently was demonstrated to have culture confirmed prostate abscess. The culture of drained prostate pus grew Brucella melitensis.…”
mentioning
confidence: 99%